Clinical Evidence Informing Treatment Guidelines on Repurposed Drugs for Hospitalized Patients During the Early COVID-19 Pandemic: Corticosteroids, Anticoagulants, (Hydroxy)chloroquine - Wüstner, Stefanie; Hogger, Sara; Gartner-Freyer, Daniela; Lebioda, Andrea; Schley, Katharina; Leverkus, Friedhelm (Frontiers in Public Health, 2022)
Introduction In early 2020, the coronavirus disease 2019 (COVID-19) pandemic spread worldwide, overwhelming hospitals with severely ill patients and posing the urgent need for clinical evidence to guide patient care. First treatment options available were repurposed drugs to fight inflammation, coagulopathy, and viral replication. A vast number of clinical studies were launched globally to test their efficacy and safety. Our analysis describes the development of global evidence on repurposed drugs, in particular corticosteroids, anticoagulants, and (hydroxy)chloroquine in hospitalized COVID-19 patients based on different study types. We track the incorporation of clinical data in international and national treatment guidelines and identify factors that characterize studies and analyses with the greatest impact on treatment recommendations. Methods A literature search in MEDLINE was conducted to assess the clinical evidence on treatment with corticosteroids, anticoagulants, and (hydroxy)chloroquine in hospitalized COVID-19 patients during the first year of the pandemic. Adoption of the evidence from this clinical data in treatment guidelines of the World Health Organization (WHO), Germany, and United States (US) was evaluated over time. Results We identified 106 studies on corticosteroids, 141 studies on anticoagulants, and 115 studies on (hydroxy)chloroquine. Most studies were retrospective cohort studies; some were randomized clinical trials (RCTs), and a few were platform trials. These studies were compared to studies directly and indirectly referred to in WHO (7 versions), German (5 versions), and US (21 versions) guidelines. We found that initially large, well-adjusted, mainly retrospective cohort studies and ultimately large platform trials or coordinated meta-analyses of RCTs provided best available clinical evidence supporting treatment recommendations. Discussion Particularly early in the pandemic, evidence for the efficacy and safety of repurposed drugs was of low quality, since time and scientific rigor seemed to be competing factors. Pandemic preparedness, coordinated efforts, and combined analyses were crucial to generating timely and robust clinical evidence that informed national and international treatment guidelines on corticosteroids, anticoagulants, and (hydroxy)chloroquine. Multi-arm platform trials with master protocols and coordinated meta-analyses proved particularly successful, with researchers joining forces to answer the most pressing questions as quickly as possible.